Financial Statement Analysis Ratios for Evaluating Performance Efficiency of Saudi manufacturing companies (Case Study: Saudi Arabian Oil Company - A Saudi Joint Stock Company) (Study in Financial Analysis) - Mohammed Abdullah Al-Mekhlafi (Migration Letters, 2023)
Purpose of Research: The purpose of this research was to analyze and interpret the financial ratios of the Saudi Arabian Oil Company (Saudi Joint Stock Company) to assess the company’s strengths and weaknesses and provide any conclusions or recommendations that would be appropriate in light of the findings. Research Design: The research method is the “financial analysis” of the financial statements: consolidated balance sheet and consolidated statement of income of Saudi Arabian Oil Company, which is historical data from (2017–2021), and draw conclusions. Methods for Collecting Data: Both secondary and primary sources must be used to gather data for this research. - Secondary Data Sources: The information found in books, periodicals, theses, articles, and a few useful websites was represented by secondary sources. The theoretical framework was established after carefully examining the pertinent literature. - Primary Data Sources: The study’s required data is being gathered from the financial statements: consolidated balance sheet and consolidated statement of income of Saudi Arabian Oil Company’s annual reports (2017-2021). Findings: This study revealed that the company’s capacity was adequate to pay its short-term obligations at maturity by cash without sell of any other current assets. The business generated (2017-2021) enough gross profits to cover all costs, and generated net income. The company’s net profit significantly decreased in 2020 due to a decline in net sales and an increase in financing costs; the reduction in net sales is attributed to the coronavirus (covid-19). Recommendations: The researcher recommended using financial ratios to conduct research on other businesses that engage in similar activities to the Saudi Arabian Oil Company, exploring how the coronavirus (covid-19) affects the performance of commercial, industrial, and service companies, and teaching university students how to analyze a company’s performance efficiency by using financial ratios.